2021
DOI: 10.1021/acsnanoscienceau.1c00010
|View full text |Cite
|
Sign up to set email alerts
|

Design of Over-1000 nm Near-Infrared Fluorescent Polymeric Micellar Nanoparticles by Matching the Solubility Parameter of the Core Polymer and Dye

Abstract: Polymeric micellar nanoparticles (PNPs) encapsulating over-thousand-nanometer (OTN) near-infrared (NIR) fluorescent dye molecules in block polymers having hydrophobic and hydrophilic chains are promising agents for the dynamic imaging of deep tissue. To achieve OTN-NIR fluorescent PNPs (OTN-PNPs) having high brightness, it is crucial to increase the affinity between the core polymer and dye molecules by matching their polarities; thus, criteria and methods to evaluate the affinity are required. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 37 publications
(59 reference statements)
0
21
0
Order By: Relevance
“…For designing highly fluorescent nanoparticles encapsulating IR-1061, a quantitative evaluation of the affinity of the dye molecule and the core polymer is useful, which can be estimated using solubility parameters. Previous studies have demonstrated that matching the solubility parameters of dyes and core polymers realizes the design of high-performance fluorescent polymeric micellar nanoparticles containing hydrophobic dyes [ 57 ], as shown in Figure 2 a. The Hansen solubility parameter (HSP) is described by three components—dispersion, polarity, and hydrogen bonding separately [ 58 , 59 ] (see Section 3 for details)—and thus allows quantitative consideration of the polarity of molecules.…”
Section: Dye-loaded Nanostructure For Nir Fluorescencementioning
confidence: 99%
See 3 more Smart Citations
“…For designing highly fluorescent nanoparticles encapsulating IR-1061, a quantitative evaluation of the affinity of the dye molecule and the core polymer is useful, which can be estimated using solubility parameters. Previous studies have demonstrated that matching the solubility parameters of dyes and core polymers realizes the design of high-performance fluorescent polymeric micellar nanoparticles containing hydrophobic dyes [ 57 ], as shown in Figure 2 a. The Hansen solubility parameter (HSP) is described by three components—dispersion, polarity, and hydrogen bonding separately [ 58 , 59 ] (see Section 3 for details)—and thus allows quantitative consideration of the polarity of molecules.…”
Section: Dye-loaded Nanostructure For Nir Fluorescencementioning
confidence: 99%
“…The HSPs of dye molecules, even if they are an ionic compound such as IR-1061, can be calculated by the Hansen solubility sphere method [ 65 ] from the results of solubility tests in various organic solvents. When a micellar nanoparticle is composed of a polymer core having a chemical structure with a small energy difference from the dye molecule IR-1061, based on the three factors of dispersion, polarity, and hydrogen bonding, the nanoparticle encapsulates the dye with high efficiency and provides a probe with high fluorescence performance and encapsulation stability [ 57 ]. Note that the increased affinity between the dye and the polymer prevents the invasion of water molecules that can couple with IR-1061 as a quencher into the hydrophobic core of polymer micelles.…”
Section: Dye-loaded Nanostructure For Nir Fluorescencementioning
confidence: 99%
See 2 more Smart Citations
“…Poly(lactic acid) (PLA), a well-known biocompatible and biodegradable polymer that is widely used to make fluorescent probes and drug delivery carriers in biomedical research, 40–44 is well-suited for IR-1061 encapsulation based on its solubility parameter. 32 Since lactic acid exists in two optical isomeric forms, l -lactate and d -lactate, there are different types of PLA: poly( dl -lactic acid), a d - and l -lactic acid copolymer (PDLLA); poly( l -lactic acid) (PLLA); and poly( d -lactic acid) (PDLA). While only PDLLA was used in our previous study, 32 it has a different crystallinity from enantiomerically homogenous PLLA and PDLA 45 and may show different imaging results of tumors as suggested when loaded with indocyanine green.…”
Section: Introductionmentioning
confidence: 99%